Statistical analysis of the migration situation and the factors affecting the Russian demographic expansion - Pavel E. Prokhorov; Nikita D. Epstein (Статистика и экономика)
The article is devoted to actual factors influencing the demographic expansion processes. The purpose of the study is to examine the characteristics and problems quantify the factors in the formation of migration flows in modern Russia. Migration has always existed, but over the past two centuries, both worldwide and in Russia, migration flows have undergone unprecedented quantitative and qualitative transformation. Migration was modified from the irregular movement of the population due to the military and religious conflicts, or in search of a new place of work, in a stable and large-scale social process. Clearly, what is required to develop special demographic and socio-economic programs, the rationale for which it is impossible to fracture the situation and improve the reproductive parameters of the Russian population at both the federal and regional levels, with no in-depth statistical analyzes. For this reason, statistical evaluation of the level and dynamics of private and integral indicators of demographic security is of great scientific and practical interest. However, unfortunately, we must note that there are still many questions about the methodology of statistical research of demographic security of the state have not reached an adequate level of scientific study, and does not fully correspond to the complexity of problems solved today. Problems of this kind is clearly holding back the pace of socio-economic development of modern Russia, and therefore urgently require the development of special programs aimed at optimizing the situation in the migratory movement of the population. It is obvious that their rationale is impossible without complex statistical studies that urgently require a systematic improvement of applied analysis algorithms associated with a comprehensive quantitative assessment of the characteristics and outcomes of territorial displacement of people. In the study a critical assessment of the current classification of the factors, which affecting the migratory processes in Russia, has been carried out on the basis of the logical method of analysis of the subject area. With the use of quantitative methods for measuring the socio-economic processes and systems, the amount of the demographic expansion of the Russian population has been described. Using the absolute and relative quantities characterizing the change of the object in time, the direction and scale of the evolutionary processes of international demographic expansion in the Russian Federation have been identified. Based on the official data the coefficient of migration attractiveness of Russia was calculated, and the absolute and relative performance of domestic and international migration were estimated by regions.In general, the above arguments, we believe, indicate that the improvement of the statistical methodology of the research level, factors of various aspects of the demographic expansion of the population of the Russian Federation is an important task, which is of great practical importance.